Vorinostat or placebo in combination with bortezomib in patients with multiple myeloma (VANTAGE 088): a multicentre, randomised, double-blind study - Dimopoulos, Meletios A.; Siegel, David S; Lonial, Sagar; Qi, Junyuan; Hajek, Roman; Facon, Thierry; Rosinol, Laura; Williams, Catherine; Blacklock, Hilary; Goldschmidt, Hartmut; Hungria, Vania; Spencer, Andrew; et al. (The lancet. Oncology, 2013)
Background - We aimed to assess efficacy and tolerability of vorinostat in combination with bortezomib for treatment of patients with relapsed or refractory multiple myeloma. - Methods - In our randomised, double-blind, placebo-controlled, phase 3 trial, we enrolled adults (≥18 years) at 174 university hospitals in 31 countries worldwide. Eligible patients had to have non-refractory multiple myeloma that previously responded to treatment (one to three regimens) but were currently progressing, ECOG performance statuses of 2 or less, and no continuing toxic effects from previous treatment. We excluded patients with known resistance to bortezomib. We randomly allocated patients (1:1) using an interactive voice response system to receive 21 day cycles of bortezomib (1·3 mg/m2 intravenously on days 1, 4, 8, and 11) in combination with oral vorinostat (400 mg) or matching placebo once-daily on days 1-14. We stratified patients by baseline tumour stage (International Staging System stage 1 or stage ≥2), previous bone-marrow transplantation (yes or no), and number of previous regimens (1 or ≥2). The primary endpoint was progression-free survival (PFS) in the intention-to-treat population. We assessed adverse events in all patients who received at least one dose of study drug. This study is registered with ClinicalTrials.gov, number 00773747. - Findings - Between Dec 24, 2008, and Sept 8, 2011, we randomly allocated 317 eligible patients to the vorinostat group (315 of whom received at least one dose) and 320 to the placebo group (all of whom received at least one dose). Median PFS was 7·63 months (95% CI 6·87-8·40) in the vorinostat group and 6·83 months (5·67-7·73) in the placebo group (hazard ratio [HR] 0·77, 95% CI 0·64-0·94; p=0·0100). 312 (99%) of 315 patients in the vorinostat group and 315 (98%) of 320 patients in the placebo group had adverse events (300 [95%] adverse events in the vorinostat group and 282 [88%] in the control group were regarded as related to treatment). The most common grade 3-4 adverse events were thrombocytopenia (143 [45%] patients in the vorinostat group vs 77 [24%] patients in the placebo group), neutropenia (89 [28%] vs 80 [25%]), and anaemia (53 [17%] vs 40 [13%]). - Interpretation - Although the combination of vorinostat and bortezomib prolonged PFS relative to bortezomib and placebo, the clinical relevance of the difference in PFS between the two groups is not clear. Different treatment schedules of bortezomib and vorinostat might improve tolerability and enhance activity. - Funding - Merck.
Gesehen am 16.12.2020